Pengembangan Media FLISISPENSA (Flipbook Sistem Pencernaan Manusia) terhadap Peningkatan Literasi Sains Siswa Sekolah Dasar - Shinta Yuliana Pratiwi; Endang Indarini (JANACITTA, 2025)
Abstract The purpose of this research and development is to describe the development of media, the level of media validity, the effectiveness of the media, and the practicality of FLISISPENSA (Human Digestive System Flipbook) media towards increasing elementary students' science literacy. The method used in this research is Research and Development (R&D) with the ADDIE development model. The stages in this development research include problem identification, data collection, product design, product design validation, product design revision, field trials, and evaluation. The results of the validation carried out by material experts show a percentage score of 96% with a “very high” category, while for media experts get a percentage rate of 94.66% with a “very high” category, and for learning design experts receive a score of 94% with a “very high” category. The effectiveness of the media is seen from the results of the T Test which produces a sig. value of 0.001, which is smaller than 0.05, so it can be concluded that there is an increase in the value of science literacy from 64% to 86%. Meanwhile, the results of practicality based on student assessment reached a percentage of 87.37% with the criteria “very practical”, and according to the teacher's assessment got a percentage of 97% with the category “very practical”. Abstrak Tujuan penelitian dan pengembangan ini adalah untuk mendeskripsikan pengembangan media, tingkat validitas media, keefektifan media, dan kepraktisan media FLISISPENSA (Flipbook Sistem Pencernaan Manusia) terhadap peningkatan literasi sains siswa SD. Metode yang digunakan dalam penelitian ini adalah Research and Development (R&D) dengan model pengembangan ADDIE. Tahapan dalam penelitian pengembangan ini mencakup identifikasi permasalahan, pengumpulan data, desain produk, validasi desain produk, revisi desain produk, uji coba lapangan, dan evaluasi. Hasil dari validasi yang dilakukan oleh ahli materi menunjukkan persentase skor sebesar 96% dengan kategori “sangat tinggi”, sementara untuk ahli media mendapatkan angka persentase 94,66% dengan kategori “sangat tinggi”, dan untuk ahli desain pembelajaran menerima skor 94% dengan kategori “sangat tinggi”. Efektivitas media terlihat dari hasil uji T Test yang menghasilkan nilai sig. sebesar 0.001, yang lebih kecil dari 0.05, sehingga dapat disimpulkan terdapat peningkatan dalam nilai literasi sains dari 64% menjadi 86%. Sedangkan, hasil kepraktisan berdasarkan penilaian siswa mencapai persentase 87,37% dengan kriteria “sangat praktis”, dan menurut penilaian guru mendapatkan persentase 97% dengan kategori “sangat praktis”.